2005
DOI: 10.1529/biophysj.105.062984
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Role of Calcium Store-Dependent Plasma Membrane Calcium Channels in Action-Potential Firing and Intracellular Calcium Oscillations

Abstract: In many biological systems, cells display spontaneous calcium oscillations (CaOs) and repetitive action-potential firing. These phenomena have been described separately by models for intracellular inositol trisphosphate (IP3)-mediated CaOs and for plasma membrane excitability. In this study, we present an integrated model that combines an excitable membrane with an IP3-mediated intracellular calcium oscillator. The IP3 receptor is described as an endoplasmic reticulum (ER) calcium channel with open and close p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 56 publications
(106 reference statements)
1
28
0
Order By: Relevance
“…In previous studies, we have reported a mathematical model of NRK fibroblasts capturing the basic characteristics (27,28) based on single-cell data (14). This model was obtained by implementation of the dynamics of the membrane ion channels and the intracellular calcium oscillator.…”
Section: Model Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, we have reported a mathematical model of NRK fibroblasts capturing the basic characteristics (27,28) based on single-cell data (14). This model was obtained by implementation of the dynamics of the membrane ion channels and the intracellular calcium oscillator.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The key idea of the model (27) is that autocrine and paracrine production of hormones such as PGF 2␣ leads to the production of IP3, which gives rise to IP 3-mediated intracellular calcium oscillations. These IP 3-mediated calcium oscillations cause periodic calcium transients, which open the Cl Ca channels.…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations